POSITIVE VALUE OF COVID 19 PANDEMIC FOR MSMEs: A CASE STUDY IN YOGYAKARTA - Sugiyanto Sugiyanto; Dewi Suma; Prayeki Prayeki (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The research entitled the positive value of the covid-19 pandemic for MSMEs in Yogyakarta City was motivated by the covid-19 pandemic in Indonesia, starting with the findings of Covid-19 sufferers on March 2, 2020 to April 18, 2020, 6,248 confirmed positive cases of Covid-19 with 631 recovered cases and 535 died cases. As a result of the Covid-19 pandemic, the Government has established various policies such as social distancing, PSBB, learning-working-worshiping at home. The impact of the policy was that various social, tourism and economic activities stagnated. The impact of this stagnation has an impact on MSME actors in general, including MSMEs in Yogyakarta. A qualitative research approach is a case study of MSME actors who are gathered in the home business camp (HBC) and Karang Mitra Usaha (KaMU) in Yogyakarta City. Data were collected through interviews via social media, observation and literature study. Qualitative data analysis used the Creswell 2016 technique. The conclusion of the research was that the reasons behind positive thinking for MSMEs as a result of the Covid-19 epidemic were religious, psychological and educational factors. So that MSME players can take lessons by innovating, evaluating business and developing creativity. Suggestions in research, this research needs to be continued with wider informance and post-Covid-19 MSME actors need to be strengthened through disaster management training for advanced creativity development, psychology, entrepreneurial religiosity and business philosophy. Keywords: positive value, COVID-19 pandemic, MSMEs Yogyakarta